Geographies of Asylum in Europe and the Role of European Localities - Glorius, Birgit; Doomernik, Jeroen (IMISCOE Research Series,, 2020)
This open access book describes how the numerous arrivals of asylum seekers since 2015 shaped reception and integration processes in Europe. It addresses the structuration of asylum and reception systems, and spaces and places of reception on European, national, regional and local level. It also analyses perceptions and discourses on asylum and refugees, their evolvement and the consequences for policy development. Furthermore, it examines practices and policy developments in the field of refugee reception and integration. The volume shows and explains a variety of refugee reception and integration strategies and practices as specific outcome of multilevel governance processes in Europe. By addressing and contextualizing those multiple experiences of asylum seeker reception, the book is a valuable contribution to the literature on migration and integration, societal development and political culture in Europe.